2018
DOI: 10.14740/jocmr3399w
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Role for Diagonal Coronary Artery Stenting in Patients Undergoing Robotic Coronary Artery Bypass Graft Surgery?

Abstract: BackgroundThe efficacy of diagonal coronary artery stenting in patients undergoing robotic left internal thoracic artery-to-left anterior descending (LITA-to-LAD) anastomosis is not well defined. The objective of this study was to assess graft and stent patency in a single-stage hybrid revascularization with LITA-to-LAD anastomosis and PCI to a diagonal coronary artery.MethodsFrom 2004 to 2014, a total of 25 patients consented to robotic-assisted LITA harvesting and a small left anterior thoracotomy for off-pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The outcomes and the advantages of SVG have been demonstrated by past research [An 2018;Christenson 1997;Xiao 2015;Kim 2011;Ouzounian 2010]. Similarly, the risk factors that may influence the patency of GSV grafts also have been thoroughly investigated.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The outcomes and the advantages of SVG have been demonstrated by past research [An 2018;Christenson 1997;Xiao 2015;Kim 2011;Ouzounian 2010]. Similarly, the risk factors that may influence the patency of GSV grafts also have been thoroughly investigated.…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, the results of this study did not indicate that D1 bypass grafting brought any additional benefits. It may possible to partially explain these results based on previous research which found that if the diagonal branch did not have significant stenosis, then the flow of a diagonal branch bypass graft may compete with that of a LIMA graft [Koyama 2014;Nagendran 2018]. However, in cases of unsatisfactory LIMA to LAD bypass grafting that may be due to the poor quality of the LIMA graft or hostile LAD anatomy, or to a bifurcating lesion of the LAD and diagonal branch, sequential bypass grafting to the diagonal branch should be a reasonable choice [Nagendran 2018;Yajima 2017].…”
Section: E5mentioning
confidence: 99%
See 1 more Smart Citation
“…This in turn leads to faster postoperative recovery and a return to baseline activities. [1][2][3]5,[8][9][10] Moreover, cardiopulmonary bypass (CPB) is avoided, thus leading to a reduction in invasiveness and associated systemic inflammation. 11 Additionally, the possibility of adopting robotic technologies in these procedures decreased the risk of vessel injury during left internal mammary artery (LIMA) harvesting process.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the avoidance of sternotomy, there is a reduction in blood transfusion requirement, shorter intensive care unit (ICU) and hospital stay, lower time on mechanical ventilation, very low morbidity rate. This in turn leads to faster postoperative recovery and a return to baseline activities 1–3,5,8–10 . Moreover, cardiopulmonary bypass (CPB) is avoided, thus leading to a reduction in invasiveness and associated systemic inflammation 11 .…”
Section: Introductionmentioning
confidence: 99%